Exploring the Adaptive Capacity of Sugarcane Contract Farming Schemes in the Face of Extreme Events - Henriksson, Rebecka; Vincent, Katharine; Naidoo, Kivana (Frontiers in Climate, 2021)
Adaptive capacity determines the extent to which exposure to natural hazards and extreme events translates into impacts. This study traces the effectiveness of adaptive capacity of two different sugarcane contract farming schemes (so-called outgrower schemes) - Phata and Kasinthula - in Chikwawa district in southern Malawi which, due to their proximity, are similarly exposed to extreme events, but have shown different impacts in terms of sugarcane production. We develop a framework to explore and compare the adaptive capacity at scheme management level, and relate the findings to the historical changes in yield, the occurrence of extreme events in the district and the lived experiences of the scheme management over the last ten years (2010-2019) using qualitative data from interviews with scheme managers. The total level and components of adaptive capacity differ in several aspects. Phata had much better prerequisites to mitigate the impacts of the extreme events (i.e. maintain production), particularly related to the Asset base, Knowledge and information, Innovation, and Forward-looking decision-making. Kasinthula on the other hand, was impacted by compound events whilst having low financial capacity, weak governance and reduced human capacity. Kasinthula had limited capacity to recover from the severe 2015 floods, the adaptive capacity thus drawn upon and were not restored when next event occurred (drought). This novel, comparative approach to assessing adaptive capacity, linking to past events, has been shown useful in order to determine the components that are missing and need to be built in order to reduce risk from extreme events and climate change. These findings are important to ensure future adaptation of sugarcane outgrowers, and relevant also to other contract farming arrangements or similar kinds of agricultural organizations.